Gd-metallofullerenol nanomaterial as non-toxic breast cancer stem cell-specific inhibitor - Liu, Ying; Chen, Chunying; Qian, Pengxu; Lu, Xuefei; Sun, Baoyun; Zhang, Xiao; Wang, Liming; Gao, Xingfa; Li, Han; Chen, Zhiyun; Tang, Jinglong; Zhang, Weijie; et al. (Nature communications, 2015)
The contemporary use of nanomedicines for cancer treatment has been largely limited to serving as carriers for existing therapeutic agents. Here, we provide definitive evidence that, the metallofullerenol nanomaterial Gd@C 82 (OH) 22 , while essentially not toxic to normal mammary epithelial cells, possesses intrinsic inhibitory activity against triple-negative breast cancer cells. Gd@C 82 (OH) 22 blocks epithelial-to-mesenchymal transition with resultant efficient elimination of breast cancer stem cells (CSCs) resulting in abrogation of tumour initiation and metastasis. In normoxic conditions, Gd@C 82 (OH) 22 mediates these effects by blocking TGF-β signalling. Moreover, under hypoxic conditions found in the tumour microenvironment, cellular uptake of Gd@C 82 (OH) 22 is facilitated where it functions as a bi-potent inhibitor of HIF-1α and TGF-β activities, enhancing CSC elimination. These studies indicate that nanomaterials can be engineered to directly target CSCs. Thus, Gd-metallofullerenol is identified as a kind of non-toxic CSC specific inhibitors with significant therapeutic potential. A metallofullerenol nanomaterial, Gd@C 82 (OH) 22 , was shown to inhibit growth of several solid cancers in preclinical models and yet exhibit low toxicity. Herein the authors show that Gd@C 82 (OH) 22 functions as an inhibitor of breast cancer stem cell function via blocking TGF-β and HIF-1α signalling, while sparing normal tissue.